A randomized phase II study to investigate the addition of PD-L1 antibody MEDI4673 (durvalumab) to a taxane-anthracycline containing chemotherapy in triple negative breast cancer (GeparNuevo) - Loibl, Sibylle; Schneeweiss, Andreas (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Chemotherapy (CT) is the only treatment option in triple negative breast cancer (TNBC) since so far no targeted agents are available. High amounts of tumor infiltrating lymphocytes (TILs) in TNBC are associated with higher treatment response and better outcome. Immunotherapy alone or in combination might be used to increase pathological complete response (pCR, ypT0 ypN0). Adding an anti-PD-L1 checkpoint inhibitor (Durvalumab) to standard CT might be a valid option.Trial design: GeparNuevo will randomize patients to Durvalumab 1500 mg i.v. or placebo every 4 weeks. Monotherapy (750 mg i.v.) is given for the first 2 weeks (window phase), followed by a biopsy and Durvalumab/placebo plus nab-paclitaxel (nP) 125 mg/m2 weekly for 12 weeks followed by Durvalumab/placebo plus epirubicin/cyclophosphamide every 2 weeks for...